Regulatory Compliance Requirements for an Open Source Electronic Image Trial Management System - Rhodes, Colin (Conf Proc IEEE Eng Med Biol Soc, 2010)
There is a global need for software to manage imaging based clinical trials to speed basic research and drug development. Such a system must comply with regulatory requirements. The U.S. Food and Drug Administration (FDA) has regulations regarding software development process controls and data provenance tracking. A key unanswered problem is the identification of which data changes are significant given a workflow model for image trial management. We report on the results of our study of provenance tracking requirements and define an architecture and software development process that meets U.S. regulatory requirements using open source software components.